PERAN PEMERINTAH DALAM MENYELAMATKAN USAHA MIKRO, KECIL, DAN MENENGAH DI ERA PANDEMI COVID-19 (Sebuah Kajian dalam Perspektif Ekonomi Islam) - Adlan, Muhamad Aqim (UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This study aims to see the role and steps of the government in saving micro, small and medium enterprises (UMKM) from an Islamic economic perspective. This is based on the era of the COVID-19 pandemic, the economic sector (UMKM) is one of the sectors that is experiencing problems. So that this condition requires a step and the role of the government in responding to the problems above. This study is a library research study which aims to see the role of the government in saving the UMKM sector from an Islamic economic perspective. The findings in this study indicate that: First, the role of the Indonesian government in saving the UMKM sector in the era of the COVID-19 pandemic by issuing policies in the form of assistance and assistance to UMKM players and conducting a pre-work card program. Second, from the perspective of Islamic economics, the role of the government in saving the UMKM sector is a manifestation of the fundamental values of the Islamic economic concept.